this is another question.
what i tried to do is :
x=b,
(b^2) + pb +q = 3(b^2) +q
-2(b^2) + pb = 0
and then.....i'm stuck. ="=
i think my beginning is already incorrect. =_=
this is another question.
what i tried to do is :
x=b,
(b^2) + pb +q = 3(b^2) +q
-2(b^2) + pb = 0
and then.....i'm stuck. ="=
i think my beginning is already incorrect. =_=
A tip: Always use new threads for new questions. Your problem will get attention faster. People always tend to answer new posts than old ones.
Instead of the above equation, write it as:
(b^2) + pb +q = 0; --------------------------(1)
3(b^2) +q = 0;--------------------------(2)
Multiply the first equation by 3 and subtract the second from it.
$\displaystyle (3b^2 + 3pb + 3q) - (3b^2 +q ) = 0$$\displaystyle \Rightarrow 3pb + 2q = 0 \Rightarrow 9p^2b^2 = 4q^2 $
Now eliminate $\displaystyle b^2$ from the above equation and equation (2).